Evaluation of Business Model Transformation: A Case Study in Trading Company PT. S - Sondang Eka Rahmawati; Lindawati Gani (Budapest International Research and Critics University, 2022)
PT. S has been trading on imported food coloring and flavorings in Indonesia for over seventeen years. Specifically, it is a subsidiary of a multi-corporate organization that boosts the latest technology in the food coloring industry. Although the Indonesian market for food and beverages is still growing, PT. S has not been performing well in recent years. The inefficient local operational and management activities forced its head office to change its strategy to survive and remain competitive in the industry. The poor performance has prompted a change in the business model, leading to a shift from the direct sales methods to the utilization of distributors. Therefore, this study aimed to evaluate the impact of change in the business model. A descriptive qualitative model with the case study method and a single unit for analysis were used. The data was collected through observation, a document study, and interviews. Furthermore, the triangulation method was used to process the data, which was then analyzed through value chain analysis and strategic cost management. The analysis also focused on activity-based cost management and customer profitability. The result showed that this business model successfully improves the company’s financial performance, though several processes need further attention.